Jual Beli Tanah Tidak Bersertifikat dalam Perspektif Hukum Agraria Indonesia (Studi di Kecamatan Palabuhanratu Kabupaten Sukabumi) - Muhammad Alrizky Ekiawan; Teddy Lesmana (CV Rewang Rencang, 2023)
One problem that often occurs in buying and selling transactions like the transfer of land rights is land buying and selling transactions without certificates. Whereas a land certificate is valid and strong proof of land ownership. The research method used is descriptive analysis with a normative juridical approach. The results of the study show that there are still many people who buy and sell land that is not certified. This is due to a lack of understanding of the importance of land certificates even though this has risks and legal consequences, such as the absence of a transfer of land rights or the invalidity of the related transfer and the absence of guarantees for legal certainty and legal protection.